Assessing the Level of Competencies Among Emergency Room Nurses During Code Blue Events - Torrizo, Arvic (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the competency levels of emergency room nurses during code blue events and determined whether demographic variables significantly influenced their perceived competencies. It was anchored on Patricia Benner’s Novice to Expert Nursing Theory, Role Theory, Teamwork Theory, and the Input–Process–Output model, which framed competency and role clarity as outcomes of professional development, role understanding, and interprofessional collaboration. The study employed a descriptive correlational research design and was conducted in a private Level II hospital in Pasig City, Philippines. The respondents were registered nurses assigned to the emergency department who were directly involved in code blue responses. Data were gathered using a structured questionnaire that measured demographic profile and perceived competency during code blue events in terms of knowledge, skills, and attitude. Descriptive statistics summarized respondent characteristics and competency levels, while correlation analysis determined the relationship between demographic variables and competency domains. Findings showed that the emergency room nurse respondents were mostly young, largely college graduates, and predominantly early-career nurses, with most having attended relevant code blue training. The respondents demonstrated high perceived competency across knowledge, skills, and attitude domains. In the knowledge domain, they showed strong understanding of advanced cardiac life support principles, medication administration, post-resuscitation care, ethical considerations, and hospital code blue activation procedures, although rhythm recognition, infection control during resuscitation, and airway management required continued reinforcement. In the skills domain, nurses reported very high competence in performing chest compressions, ventilation, emergency medication administration, patient safety practices, defibrillator operation, and teamwork, while prompt activation and documentation accuracy were identified as areas for procedural improvement. In the attitude domain, respondents demonstrated professionalism, accountability, teamwork orientation, calmness, patient-centeredness, motivation for improvement, and reflective practice, although acceptance of constructive feedback was relatively lower. Correlation analysis revealed no significant relationship between demographic variables and perceived competency levels in knowledge, skills, and attitude. This indicates that competency during code blue events was not determined by age, gender, civil status, educational attainment, years of experience, or training attendance alone. The study concluded that emergency room nurses possess strong perceived competencies for code blue management, but targeted reinforcement is still needed in selected technical and procedural areas. The study recommended regular mock code simulations, structured post-event debriefing, standardized documentation and activation checklists, updated life support training, performance audits, and future objective or longitudinal assessments. The study aligns with SDG 3, Good Health and Well-Being, by supporting safer emergency response and patient care, and SDG 4, Quality Education, by emphasizing continuous professional development and simulation-based learning. Its sustainability impact is mainly public health, educational, institutional, and governance-related, as it supports safer hospital systems, stronger emergency preparedness, and continuous improvement in nursing practice.